Influence of external pressure on silicon electrodes in lithium-ion cells. (1st July 2022) - Göttlinger, Mara; Daubinger, Philip; Stracke, Werner; Hartmann, Sarah; Giffin, Guinevere A.
Graphical abstract: Abstract: The influence of external pressure on lithium-ion cells containing a silicon anode is investigated. The performance of pouch-type full cells under rigid compression is compared to unconstrained cells, where the electrode stack is allowed to swell during cycling. The negative electrode contains only silicon as active material, while prelithiated lithium titanium oxide (LTO) is used as the positive electrode. The results show that the main failure mechanism in such cells is a continuous irreversible consumption of lithium ions, likely due to repeated solid electrolyte interphase breakage and reformation. At high pressures, the lithium depletion has a larger influence than at lower pressures. This effect is examined by electrochemical impedance spectroscopy (EIS) and scanning electron microscopy (SEM) as well as dilation measurements of flexibly-constrained cells and can be traced back to an increase of the ionic pore resistance being more pronounced under high pressure. A new approach is used to compensate the lithium loss, i.e. internal relithiation of the LTO electrode via a lithium reservoir. This not only proves the theory of irreversible lithium consumption being the main challenge in these cells, but also enables cycling for 1000 cycles at 1200 mAh g Si − 1 without capacity fading.